Perencanaan Kapasitas Produksi pada Produk Mobil Mainan Menggunakan Analisis Time Series dengan Mempertimbangkan Special Event pada Toy Manufacturing, Indonesia - Anastasia Lidya Maukar; Intan Yosa Pramisela (Jurnal Rekayasa Sistem Industri, 2023)
Toy Manufacturing Indonesia is a multinational toy company from the United States. One of the products produced is FashionD and HotW. Capacity planning, one part of production planning and control, is an efficient effort to increase the utilization of company resources. In 2021, the toy cars  demand  increased during special events, such as Thanksgiving, Black Friday, Christmas, and New Year's Eve. It occurs periodically or seasonally, showing a positive trend pattern every year. Toy Manufacturing Indonesia lost 844 thousand cars during the special event, especially at Christmas. Lost sales occur because demand has exceeded the available capacity at regular times and over time. On the other hand, there is still usable capacity during periods of no surge in demand (non-special events). It can be seen from the regular time capacity utilization in the non-special event period, 82% below the average per year. This study shows that by increasing forecasting accuracy, the transportation method's aggregate planning can increase regular time capacity utilization in non-special events by up to 90%, and all demand can be fulfilled (no lost sales). The proposed system design program uses Excel VBA Macro, which can carry out production with high capacity efficiently and effectively